Lip Synchrony of Bilabial Consonants in the Lithuanian Dubbed Live-Action Film a Dog's Way Home - Koverienė Indrė (Darnioji daugiakalbystė, 2023)
This article explores the intricate nature of lip synchrony in dubbing as an audiovisual translation mode, highlighting its significance beyond aesthetic considerations. Often overlooked during the translation process for dubbing, the mismatch between auditory and visual signals caused by unsynchronized lip movements can have a negative impact on speech perception. Moreover, with the constant rise of audiovisual content, achieving satisfactory lip synchrony remains a crucial challenge that demands attention. Although scholars such as Fodor (1976) and Chaume (2012) have recognized the importance of bilabial consonants in maintaining lip synchrony, there is a notable research gap specifically focusing on this aspect within the Lithuanian dubbed industry. To address this gap, this study investigates the lip synchrony of bilabial consonants in the Lithuanian dubbed version of the live-action film A Dog's Way Home (2019). By employing a comparative research approach that integrates qualitative and quantitative analyses, the study draws on theoretical perspectives presented by McGurk and MacDonald (1976), Fodor (1976), Chaume (2004, 2012), and Koverienė (2015). The analysis of the cinematographic shots reveals that only a small percentage (19%) of the bilabial phonemes in the source language utterances were visually prominent instances, and consequently chosen for detailed examination of lip synchrony. This finding suggests that strict adherence to lip synchrony may not be crucial in numerous instances, allowing translators to have greater flexibility in their approach. The target language utterances demonstrate a relatively high percentage (approximately 76%) of synchronous cases for bilabials, particularly in proper names and international words. However, the research also reveals additional 94 instances of bilabials in the target language that were not found in the source language utterances, leading to dischronemes. Therefore, audiovisual translators are urged to consider not only how to maintain the lip synchrony of bilabial consonants in the target language, but also how to avoid the emergence of new bilabials.